Hak Rakyat dalam Mekanisme Pembubaran Partai Politik di Indonesia - Perdana, Gema (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This paper aims to reveal the granting of authority to the people in the mechanism of dissolution of political parties and the idea of the Ius Constituendum mechanism of dissolution of political parties in Indonesia. This paper uses a normative juridical study with a historical approach, a case approach, and a statute approach. This paper shows that the granting of authority to the people in the mechanism of dissolution of Political Parties must pay attention to the people as the owner of the country’s sovereignty. The people should be qualified for having legal standing in the request to dissolve political parties. Ius Constituendum the dissolution of political parties in Indonesia becomes a model of appropriate sanctions against political parties that have violated the provisions which are proven and decided by the competent institution, in this case, the judicial institution.